版权声明:欢迎关注我的博客,本文为博主【炒饭君】原创文章,未经博主同意不得转载 https://blog.csdn.net/a1061747415/article/details/36685493
Dice
Problem Description
You have a dice with m faces, each face contains a distinct number. We assume when we tossing the dice, each face will occur randomly and uniformly. Now you have T query to answer, each query has one of the following form: 0 m n: ask for the expected number of tosses until the last n times results are all same. 1 m n: ask for the expected number of tosses until the last n consecutive results are pairwise different.
Input
The first line contains a number T.(1≤T≤100) The next T line each line contains a query as we mentioned above. (1≤m,n≤10 6) For second kind query, we guarantee n≤m. And in order to avoid potential precision issue, we guarantee the result for our query will not exceeding 10 9 in this problem.
Output
For each query, output the corresponding result. The answer will be considered correct if the absolute or relative error doesn't exceed 10 -6.
Sample Input
6 0 6 1 0 6 3 0 6 5 1 6 2 1 6 4 1 6 6 10 1 4534 25 1 1232 24 1 3213 15 1 4343 24 1 4343 9 1 65467 123 1 43434 100 1 34344 9 1 10001 15 1 1000000 2000
Sample Output
1.000000000 43.000000000 1555.000000000 2.200000000 7.600000000 83.200000000 25.586315824 26.015990037 15.176341160 24.541045769 9.027721917 127.908330426 103.975455253 9.003495515 15.056204472 4731.706620396
Source
题目大意:
m边形的骰子,问你出现连续同样(不同)n次须要掷的次数的数学期望。
解题思路:
利用递归方式的DP的思想推公式
解题代码:(1)若询问为0,则:
dp[i] 记录的是已经连续i个同样,到n个同样同须要的次数的数学期望 dp[0]= 1+dp[1] dp[1]= 1+( 1/m*dp[2]+(m-1)/m*dp[1])=1+(dp[2]+(m-1)*dp[1])/m; dp[2]= 1+(dp[3]+(m-1)*dp[2])/m; .................... dp[n]= 0 推出: dp[i] = 1 + ( (m-1)*dp[1] + dp[i+1] ) / m dp[i+1] = 1 + ( (m-1)*dp[1] + dp[i+2] ) / m 因此。m*(dp[i+1]-dp[i])=(dp[i+2]-dp[i+1]) 我们发现是等比数列 dp[0]-dp[1]=1; dp[1]-dp[2]=m; .......... dp[n-1]-dp[n]=m^(n-1) 累加,得:dp[0]-dp[n]=1+m+m^2+..........m^(n-1)=(1-m^n)/(1-m) 所以:dp[0]=(1-m^n)/(1-m); (2)若询问为1,则: dp[0] = 1 + dp[1] dp[1] = 1 + (dp[1] + (m-1) dp[2]) / m dp[2] = 1 + (dp[1] + dp[2] + (m-2) dp[3]) / m dp[i] = 1 + (dp[1] + dp[2] + ... dp[i] + (m-i)*dp[i+1]) / m dp[i+1]= 1 + (dp[1] + dp[2] + ... dp[i] + dp[i+1] + (m-i-1)*dp[i+1]) / m ... dp[n] = 0; 选出 dp[i] 和 dp[i+1] 这两行相减 得 dp[i] - dp[i+1] = (m-i-1)/m * (dp[i+1] - dp[i+2]); 因此 dp[i+1] - dp[i+2] = m/(m-i-1)*(dp[i]-dp[i+1]); 所以: dp[0]-dp[1]=1; dp[1]-dp[2]=1*m/(m-1); dp[2]-dp[3]=1*m/(m-1)*m/(m-2); .......... dp[n-1]-dp[n]=1*m/(m-1)*m/(m-2)*.......*m/(m-n+1); 累加得到答案
#include#include #include using namespace std;inline double solve(){ int op,m,n; scanf("%d%d%d",&op,&m,&n); double ans=0; if(op==0){ for(int i=0;i<=n-1;i++){ ans+=pow(1.0*m,i); } }else{ double tmp=1.0; for(int i=1;i<=n;i++){ ans+=tmp; tmp*=m*1.0/(m-i); } } return ans;}int main(){ int t; while(scanf("%d",&t)!=EOF){ while(t-- >0){ printf( "%.9lf\n",solve() ); } } return 0;}